Primary Gastrointestinal Tract Lymphoma - David Reinhard Sumantri Samosir; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Extranodular lymphomacanbe found in almostallorgan. One third of the cases found in gastrointestinal(GI) tract, whichisthemost commonformofextranodular lymphoma.All thesubtypesof lymphomamayoccurasprimarylesionalongingastrointestinaltract,butthemostcommonformis B-celldiffuse largecelllymphoma.DiseasesthatlinkedwithGItractlymphomaareinflammatorybowel disease, celiac disease,Helicobacter pylori, virus infection,collagen diseaseandionicradiation.This reportdescribed a40yearsoldmanwith recurrentbloodystoolandcolon lymphomawasblamedas the sourceofbleeding withitsmanagementoflymphoma. Keywords:lymphoma, gastrointestinaltract,extranodular